Effect of Biofuel Use on Ship Engine - Marsudi, Sugeng; Tumpu, Mula (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2024)
This research examines the effect of biofuel use on ship engine performance, with a focus on performance, efficiency and environmental impact. Experimental studies were conducted using four-stroke marine diesel engines operated with various blends of biofuels and conventional fuels. The measured parameters include engine power, specific fuel consumption, thermal efficiency, and exhaust emissions. The results showed that the use of biofuels at certain concentrations can produce performance comparable to conventional fuels, with some significant differences. Engine power decreased slightly (2-5%) at high biofuel blends, but thermal efficiency increased up to 3% at optimal blends. Specific fuel consumption increased by about 5-8% compared to conventional fuel. Exhaust emissions analysis showed a significant reduction in carbon monoxide (CO) and particulate emissions, with up to 30% and 40% reductions respectively. However, there was a slight increase in oxides of nitrogen (NOx) emissions by 5-10%. The study also identified several technical challenges in the use of biofuels, including the potential degradation of certain engine components and the need for fuel system modifications.